Perceptions of SAQA's critical cross-field outcomes as key management meta-competencies - T. Carmichael; A. Stacey (South African Journal of Business Management, 2006)
The critical cross-field outcomes (CCFOs) formulated by the South African Qualifications Authority (SAQA) are generic competencies designed to underpin all national qualifications registered on the National Qualifications Framework (NQF). They are intended to provide the basis for lifelong learning, personal growth, honest business acumen, critical, creative thinking and aesthetic appreciation. However, little work on these important learning outcomes has been published, despite their high face validity, and this exploratory study amongst MBA graduates is intended to stimulate interest and further research into this important area.Although the findings cannot necessarily be generalised due to the specific sampling methodology among 53 MBA graduates from Wits Business School (graduating between 1998 and 2002), it was found that the CCFOs were collectively important to their careers, although individually, some were considered more important than others. The sample also perceived that the CCFOs were developed through the course of their studies, with use of information being developed the most, and use of technology the least.These findings are encouraging as they imply that most of the CCFOs are intuitively important to both faculty and management students and mechanisms for systematically embedding the CCFOs into curricula may be sought and implemented to the benefit of MBA students and the business community.
Keywords: 650